The effectiveness of the explore knowledge game in improving children's interpersonal intelligence - Fadila Lailatul Isttianah; Lidya Yuliani; Apriyani; Tuti Rahmi; Utari Febriani (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aims to assess the effectiveness of Explore knowledge games in improving children's interpersonal intelligence. Exploring knowledge game is an intervention module that uses interaction in play to enhance children's interpersonal intelligence. This research used a quasi-experimental method with 28 subjects aged between 8 and 10 years. The experimental design was a Pretest-posttest control group design with a grouping technique using randomization. Data was collected using observation and analysis techniques, such as the t-test and N-Gain Score. The results of the hypothesis test show differences between the control and experimental groups after the intervention. Based on this, the explore knowledge game effectively increases children's interpersonal intelligence